Adeguacy of Internal Control System of the Seventh-Day Adventist Church-Owned Secondary Schools in the Philippines - Sundalangi, Elvis (JBE (Journal of Business and Economics); Volume 7 No.1, 2008 JBE UNKLAB, 2008)
This study examined the adequacy of internal control of the Seventh-day Adventist (SDA) Church-owned Secondary Schools in the Philippines. This study used the internal control framework suggested by Boockholdt (1996) as a basis to evaluate the adequacy of the sample schools’ internal control and studied whether they are sensitive to size of students, size of staff, size of budget, years the school has been in operation, and level of computer dependence. The adequacy of internal control is based on users’ perception and measured using Likert Scale while the sensitivity of the schools internal control to size of students, size of staff, size of budget, years the school has been in operation, and level of computer dependence is measured using Kruskall-Wallis non-parametric test. The result suggests that the SDA Church-owned Secondary Schools in the Philippines maintained an adequate internal control and that its adequacy is not sensitive to size of students, size of staff, size of budget, nor the age of the schools, however, the adequacy of internal control of the sample school is sensitive to the schools budget size.